Doing a Literature Search : a comprehensive guide for the social sciences - Hart, Chris (London : SAGE, 2001)
This text provides a practical and comprehensive guide to effectively searching the literature on any topic within the social sciences.
Index.
Keywords: Searching, Bibliographical; Database searching; Social sciences -- Information resources; Social sciences -- Research